STATUS OF REGIONAL MOOSE POPULATIONS IN EUROPEAN AND ASIATIC RUSSIA - Baskin, Leonid M (Lakehead University, 2009)
The moose population in Russia contains 4 subspecies and peaked at >800,000 animals in 1990. A substantial population decline of >50% occurred in European Russia between 1990 and 2002; populations in Asiatic Russian have remained more stable. This decline was influenced by the relationships among population densities of moose and humans, available forest habitat, and exploitation of moose. In general, fluctuations in moose populations were lower in areas with more forest habitat and lower human density.